In Vitro study of mitoxantrone and daunorubicin on human colon adenocarcinoma (HT-29) and acute promyelocytic leukemia (HL-60) cell lines - Hazirah binti Abdul Radzak
This study was done to investigate the cytotoxicity effect of commercial anticancer drugs, Mitoxantrone (Mx) and Daunorubicin (Dnr) on human colon adenocarcinoma (HT-29) and acute promyelocytic leukemia (HL-60). In this study, cell viability was determined by using MTT assay. HT-29 and HL-60 were plated at the density 1x10⁵ cell/ml/well in 96 and 6 well plates respectively. Then the cells were treated with a series of Mx and Dnr concentration (0.0, 0.4, 0.8, 1.2, 1.6 and 2.0 mM) before incubated for 24, 48 or 72 hours to obtain the IC50 ( concentration that gave 50% of cell viability). From the result, the IC50 value of Mx for HT-29 were 0.881±0.018 mM, 0.383±0.009 mM and 0.351±0.009 mM at 24,48 and 72 hours respectively. While IC50 of Mx for HL-60 were 1.592±0.009 mM, 1.572±0.009 mM and 1.192±0.006 mM at 24, 48 and 72 hours respectively. The IC50 value for Dnr was 1.923±0.002 mM 72 hours incubation time. ANOVA table showed that time and concentration were highly significant (p<0.05). This proved by Duncan test showed that there was significant different (p<0.05) between optical density mean for each incubation time and drug concentration. The IC50 concentration for drugs were used to study the effect of Mx and Dnr to cell death. The viable apoptotic and necrotic cells were viewed under flurescence microscope attached with digital camera and some necrotic cells could be seen such as, cell rupture, blebbing of cell membrane and possibly the cells shrinkage and apoptotic bodies at higher magnification. The percentage of apoptotic cells ( 24 hours: 48%, 48 hours: 48% and 72 hours: 47%) and necrotic cells ( 24 hours: 13%, 48 hours: 32% and 72 hours: 28%) are higher than those viable in HT-29 (24 hours: 19%, 48 hours: 23% and 72 hours: 21%) treated with Mx at 0.0 mM value for each incubation time. This due to some technical errors during slide preparation such as pipetting vigorously and centrifuged repeatedly. The percentage of apoptotic cells was higher compared to percentage of necrotic cells for HT-29 and HL-60 when cells treated with high concentration of Mx and Dnr. This showed that apoptosis was more favorable than necrosis. In conclusion, Mx and Dnr was potential commercial anticancer drugs against HT-29 and HL-60 for each concentration and incubation time.